2015
DOI: 10.1016/j.juro.2015.02.1202
|View full text |Cite
|
Sign up to set email alerts
|

Mp40-20 Testicular Microlithiasis in Asymtomatic Boys. What is the Appropriate Follow-Up?

Abstract: Table 2 Multivariate analysis of risk factors predicting recurrence after hydrocele repair Risk factor OR (95% CI) p-value Age 0.979 (0.945-1.014) 0.234 Incision site 9.847 (1.125-86.193) 0.039 Epididymis form 1.953 (0.355-10.734) 0.441 Patent process vaginalis 1.089 (0.133-8.923) 0.937 Hydrocele wall thickness 0.242 (0.046-1.283) 0.096

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, according to recently adopted European guidelines to scrotal imaging, sonographic follow-up is not advised in patients with isolated TML. 15,22 Similarly, a recent US study by Keenan et al 23 using a simulated cost-calculating algorithm concluded that sonographic surveillance is costly and nonefficient for such patients. Testicular self-examination is more efficient and thus recommended.…”
Section: Similarities and Differences In The Follow-up Recommendationsmentioning
confidence: 99%
“…Therefore, according to recently adopted European guidelines to scrotal imaging, sonographic follow-up is not advised in patients with isolated TML. 15,22 Similarly, a recent US study by Keenan et al 23 using a simulated cost-calculating algorithm concluded that sonographic surveillance is costly and nonefficient for such patients. Testicular self-examination is more efficient and thus recommended.…”
Section: Similarities and Differences In The Follow-up Recommendationsmentioning
confidence: 99%